Shear Characteristics of Root-Soil Interface of Caragana Korshinskii in Loess Area of Northeastern Qinghai-Tibet Plateau - Chuan Shi; Yabin Liu; Haili Zhu; Shen Liang; Lifu Xue; Shu Wang; Xiasong Hu; Guorong Li (Shuitu baochi tongbao, 2023)
[Objective] The effects of different factors on the shear strength index and shear strength of the root-soil interface were analyzed, in order to provide an understanding of the mechanism of shrub root soil fixation and slope protection in the loess region of the Northeastern Tibetan Plateau. [Methods] The dominant shrub (Caragana korshinskii) for this region was selected as the study object, and the effects of the dry density, moisture content, and salt content of soil, and of root diameter on the shear characteristics of the root-soil interface and their mechanisms were analyzed and discussed using the direct shear test (i. e., one factor was varied at a time) for root diameters of (2.20±1.00—32.00±1.80) mm and moisture contents, dry densities, and salt contents of the soil of 6.00%—22.00%, 1.20—1.60 g/cm3, and 0.59%—2.50% respectively. [Results] Root diameter had no significant effect on the shear strength indexes and shear strength of the root-soil interface (p>0.05) when other influencing factors were held constant. As soil moisture content increased from 6.00% to 22.00%, the root-soil interface cohesion initially increased and then decreased, reaching a maximum value of 6.74 kPa at a soil moisture content of 14.00%. The root-soil interface friction angle decreased linearly from 21.40° to 15.75°. The shear strength of the root-soil interface decreased linearly. As the soil dry density increased from 1.20 g/cm3 to 1.60 g/cm3, the cohesion of the root-soil interface increased exponentially from 5.70 kPa to 6.85 kPa, and the friction angle increased linearly from 20.67° to 21.67°. The shear strength of the root-soil interface increased linearly. As the soil salt content increased from 0.59% to 2.50%, the root-soil interface cohesion increased linearly from 6.71 kPa to 7.31 kPa, and the shear strength increased linearly. However, there was no significant change in the root-soil interface friction angle (p>0.05). The gray correlation analysis of these results showed that dry density had the greatest influence on the cohesion, the friction angle, and the shear strength of the root-soil interface. [Conclusion] The dry density, moisture content, and salt content of soil can all affect the shear characteristics of the root-soil interface, however, the degree of influence is different. The influence of rainfall infiltration on the shear characteristics of the root-soil interface should be fully considered when evaluating the protective effect of plant roots on the shallow soil of loess slopes.